Impact of hormonal contraception and weight loss on high‐density lipoprotein cholesterol efflux and lipoprotein particles in women with polycystic ovary syndrome. (9th March 2017) - Dokras, Anuja; Playford, Martin; Kris‐Etherton, Penny M.; Kunselman, Allen R.; Stetter, Christy M.; Williams, Nancy I.; Gnatuk, Carol L.; Estes, Stephanie J.; Sarwer, David B.; Allison, Kelly C.; Coutifaris, Christos; Mehta, Nehal; et al.
Summary: Objective: To study the effects of oral contraceptive pills (OCP), the first‐line treatment for PCOS, on high‐density lipoprotein cholesterol (HDL‐C) function (reverse cholesterol efflux capacity) and lipoprotein particles measured using nuclear magnetic resonance spectroscopy in obese women. Design: Secondary analysis of a randomized controlled trial (OWL‐PCOS) of OCP or Lifestyle (intensive Lifestyle modification) or Combined (OCP + Lifestyle) treatment groups for 16 weeks. Patients: Eighty‐seven overweight/obese women with PCOS at two academic centres. Measurements: Change in HDL‐C efflux capacity and lipoprotein particles. Results: High‐density lipoprotein cholesterol efflux capacity increased significantly at 16 weeks in the OCP group [0·11; 95% confidence interval (CI) 0·03, 0·18, P = 0·008] but not in the Lifestyle ( P = 0·39) or Combined group ( P = 0·18). After adjusting for HDL‐C and TG levels, there was significant mean change in efflux in the Combined group (0·09; 95% CI 0·01, 0·15; P = 0·01). Change in HDL‐C efflux correlated inversely with change in serum testosterone ( r s = −0·21; P = 0·05). In contrast, OCP use induced an atherogenic low‐density lipoprotein cholesterol (LDL‐C) profile with increase in small ( P = 0·006) and large LDL‐particles ( P = 0·002). Change in small LDL‐particles correlated with change in serum testosterone ( r s = −0·31, P = 0·009) and insulin sensitivity index (ISI; r s = −0·31, P = 0·02). Both Lifestyle and Combined groups did not show significant changes in the atherogenic LDL particles. Conclusions: Oral contraceptive pills use is associated with improved HDL‐C function and a concomitant atherogenic LDL‐C profile. Combination of a Lifestyle program with OCP use improved HDL‐C function and mitigated adverse effects of OCP on lipoproteins. Our study provides evidence for use of OCP in overweight/obese women with PCOS when combined with Lifestyle changes.